Meningkatkan Pemahaman Konsep Tangga Satuan Panjang melalui Penerapan Media Pembelajaran Visual pada Siswa Kelas IV SDN Keleyan 2 - Marwan 'Afif; Refania Mustaghfiroh; Wilda A’malina Zatinuha; Risma Nisa Khoirina (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2026)
This research is motivated by the lack of understanding of fourth-grade students of SDN Keleyan 2 regarding the topic of the ladder of length units, which is seen from the students' difficulties in remembering and applying the conversion of length units in everyday life. The purpose of this research is to improve students' understanding of the ladder of length units by utilizing visual learning media. The method used in this research is Classroom Action Research (CAR) which is implemented in two cycles. The subjects in this research are fourth-grade students of SDN Keleyan 2. The results of the research show significant progress in students' understanding in each cycle implemented. In the initial condition, the level of student learning completeness only reached 40%, then increased to 60% in Cycle I, and increased again to reach 84% in Cycle II. This shows that the use of visual learning media in the form of a ladder of length units is effective in improving students' understanding of the topic of conversion of length units.